Neonatal BCG Immunization Followed by DNAhsp65 Boosters: Highly Immunogenic but not Protective Against Tuberculosis - a Paradoxical Effect of the Vector? - Pelizon, A. C. [UNESP]; Martins, D. R. [UNESP]; Zorzella-Pezavento, S. F. G. [UNESP]; Seger, J. [UNESP]; Justulin, L. A. [UNESP]; da Fonseca, D. M.; Santos, R. R.; Masson, A. P.; Silva, C. L.; Sartori, Alexandrina [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
A new tuberculosis vaccine is urgently needed. Prime-boost strategies are considered very promising and the inclusion of BCG is highly desirable. In this investigation, we tested the protective efficacy of BCG delivered in the neonatal period followed by boosters in the adult phase with a DNA vaccine containing the hsp65 gene from Mycobacterium leprae (pVAXhsp65). Immune responses were characterized by serum anti-hsp65 antibody levels and IFN-gamma and IL-5 production by the spleen. Amounts of these cytokines were also determined in lung homogenates. Protective efficacy was established by the number of colony-forming units (CFU) and histopathological analysis of the lungs after challenge with Mycobacterium tuberculosis. Immunization with BCG alone triggered a significant reduction of CFU in the lungs and also clearly preserved the pulmonary parenchyma. BCG priming also increased the immunogenicity of pVAXhsp65. However, boosters with pVAXhsp65 or the empty vector abolished the protective efficacy of BCG. Also, higher IL-5 levels were produced by spleen and lungs after DNA boosters. These results demonstrated that neonatal BCG immunization followed by DNAhsp65 boosters is highly immunogenic but is not protective against tuberculosis.